Perceptions of Prospective Social Studies Teachers on the Effectiveness of Google Classroom in Enhancing Pedagogical Content Understanding and Teaching Readiness at Junior High Schools (SMP) - Sulhan Sulhan (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to analyze the perceptions of pre-service Social Studies (IPS) teachers regarding the effectiveness of using Google Classroom in improving pedagogical content knowledge and teaching readiness at the junior high school (SMP) level. The research employed a mixed-methods approach with a convergent parallel design. The participants consisted of 30 students from STKIP Harapan Bima. Quantitative data were collected through a perception questionnaire, a pedagogical understanding test, and a teaching readiness observation sheet, while qualitative data were obtained through in-depth interviews and field notes.The findings revealed a significant improvement in students’ pedagogical content understanding (mean pretest = 62.4; posttest = 79.6; p < 0.05) with an N-Gain score of 0.45 (moderate category) and an effect size of 2.15 (very strong effect). Students’ perceptions of Google Classroom effectiveness were generally high (mean = 4.19 out of 5), particularly in the dimensions of accessibility (87%) and usefulness for learning (86%). Qualitative analysis indicated that students experienced ease in accessing materials, increased collaboration, and greater efficiency in managing assignments. The main obstacles—limited internet connectivity and digital device availability—were mitigated through adaptive learning strategies.The integration of quantitative and qualitative data demonstrates that Google Classroom is effective as a pedagogical learning medium that fosters digital literacy, self-regulated learning, and professional readiness among pre-service Social Studies teachers.